High-strength high-thermal-stability Al-Cu-Mg-Si alloy and preparation method thereof
By adjusting the chemical composition and process of Al-Cu-Mg-Si alloy, the problems of insufficient matching degree of strength and toughness, corrosion resistance and insufficient thermal stability in aircraft structure applications are solved, and high strength and high thermal stability are achieved Comprehensive properties of good corrosion resistance.
Patent Information
- Application Number
- CN202411420881.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-12
AI Technical Summary
In aircraft structure applications, Al-Cu-Mg-Si alloy faces problems such as insufficient matching of strength and toughness, corrosion resistance, and insufficient thermal stability.
By adjusting the chemical composition of the alloy, controlling the Cu, Mg content and Cu/Mg ratio, increasing elements such as Mn, Cr, Zr, etc., the alloy is optimized by using two-stage homogenization, hot extrusion, solid solution quenching and stretching straightening processes such as the microstructures to improve strength and thermal stability.
The high strength and high thermal stability of the alloy were achieved, while maintaining good toughness and corrosion resistance, yield strength ≥475MPa, tensile strength ≥540MPa, elongation after breaking ≥12%, and remained after exposure at 200℃ for 100 hours. Higher performance.
Smart Images

Figure CN119433310A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloys, and in particular to a high-strength and high-thermal stability Al-Cu-Mg-Si alloy and a preparation method thereof. Background Art
[0002] Al-Cu-Mg-Si is a typical deformable and heat-treatable aluminum alloy. It is widely used in the aerospace field because of its high strength, corrosion resistance, thermal stability and forgeability. It is usually used as aircraft joints, aircraft wheels and other structural parts. With the increasing demand for lightweight and high mechanical performance materials in the automotive and aerospace industries, aluminum alloys have been increasingly used in the above industries due to their high strength-to-weight ratio, strong corrosion resistance and low cost. Although the use of composite materials has reduced the use of aluminum alloys in aircraft structures, high-strength aluminum alloys are still important aircraft materials.
[0003] For Al-Cu-Mg-Si alloy, although it has the advantages of excellent formability, corrosion resistance and low cost, it mainly faces the following problems in aircraft structure applications: insufficient matching between strength and toughness and corrosion resistance, and its thermal stability still needs to be improved due to usage scenarios. If it is possible to greatly improve the strength and thermal stability of Al-Cu-Mg-Si alloys without reducing toughness and corrosion resistance, the application scenarios and application scope of the alloy will be greatly improved, and it is even expected to replace some non-critical ultra-high-strength steel structural parts in aerospace, thereby realizing lightweight aerospace. Based on this, the present invention studies a high-strength and high-thermal stability Al-Cu-Mg-Si alloy and a preparation method thereof. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a high-strength and high-thermal stability Al-Cu-Mg-Si alloy and a preparation method thereof.
[0005] The technical solution of the present invention is as follows:
[0006] One of the purposes of the present invention is to provide an Al-Cu-Mg-Si alloy with high strength and high thermal stability. The chemical composition and mass percentage of the alloy are: Si 0.5-0.9%, Fe≤0.5%, Cu 3.9-5.0%, Mn 0.4-1.2%, Mg 0.2-0.8%, Zr 0.15-0.2%, Cr 0.1-0.2%, Ni≤0.1%, Zn≤0.25%, Ti≤0.15%, the single impurity content is ≤0.05%, the total impurity content is ≤0.15%, and Al is the balance.
[0007] Furthermore, the chemical composition and mass percentage of the alloy are: Si 0.6-0.8%, Fe≤0.3%, Cu4.4-4.8%, Mn 0.8-1.1%, Mg 0.45-0.6%, Zr 0.15-0.18%, Cr 0.1-0.15%, Ni≤0.1%, Zn≤0.2%, Ti≤0.1%, and the Cu / Mg ratio is 8-10, the Fe / Ni ratio is ≤2.5, the single impurity content is ≤0.05%, the total impurity content is ≤0.15%, and Al is the balance.
[0008] Furthermore, the yield strength of the Al-Cu-Mg-Si alloy is ≥475MPa, the tensile strength is ≥540MPa, and the elongation after fracture is ≥12%; and after exposure at 200°C for 100h, its tensile strength is ≥210MPa, the yield strength is ≥188MPa, and the exfoliation corrosion grade is EB.
[0009] The second object of the present invention is to provide a method for preparing a high-strength and high-thermal stability Al-Cu-Mg-Si alloy, comprising the steps of:
[0010] S1. Preset the chemical composition range of Al-Cu-Mg-Si alloy, then use Jmatpro software to simulate the relationship between chemical composition ratio and performance, and determine the optimal chemical composition range of Al-Cu-Mg-Si alloy according to the matching degree of strength, toughness, corrosion resistance and thermal stability;
[0011] S2, according to the chemical composition range determined in step S1, the raw materials are melted and cast to obtain an Al-Cu-Mg-Si alloy ingot;
[0012] S3, homogenizing the Al-Cu-Mg-Si alloy ingot;
[0013] S4, sawing the homogenized Al-Cu-Mg-Si alloy ingot into aluminum bars, and hot extruding them to obtain extruded profiles;
[0014] S5, performing a solution treatment on the extruded profile at a solution temperature, and quenching to room temperature after the solution treatment;
[0015] S6, stretching and straightening the extruded profile after solution treatment and quenching treatment;
[0016] S7. Performing aging treatment on the stretched extruded profile, and then air-cooling to room temperature to obtain an Al-Cu-Mg-Si alloy profile.
[0017] Furthermore, in step S2, the melt temperature is controlled to be ≤745°C during the smelting process, and the melt temperature in the smelting furnace before the melt is transferred from the smelting furnace to the refining furnace is 740±5°C; the melt temperature of the charge reaches 700°C as the start time of the melt staying in the smelting furnace, and the start time of the converter is the end time of the melt staying in the smelting furnace. The melt staying time in the smelting furnace is controlled not to exceed 8 hours, and re-stirring and sampling are required if the specified time is exceeded;
[0018] During the casting process, the casting water temperature is 18-23°C, the starting temperature is 735-745°C, the casting temperature is 685-705°C, the casting speed is 31-35mm / min, and the water flow rate is 34-40m 3 / h; and during the casting process, the aluminum liquid temperature at the outlet of the holding furnace is controlled to be ≤750℃, and the casting temperature at the hot end of the flow plate is 695±10℃.
[0019] Furthermore, in step S3, the homogenization treatment adopts a two-stage homogenization process, in which the first stage is heated to 485±5°C at a heating rate of 35-50°C / h and kept warm for 10-12h; the second stage is heated to 495±5°C at a heating rate of 15-25°C / h and kept warm for 5-8h.
[0020] Furthermore, in step S4, during hot extrusion, the mold insulation temperature is set to 385-415°C, the insulation time is 4-36h, the inner layer heating temperature of the extrusion barrel is 405-435°C, the aluminum rod insulation temperature is 370-400°C, the extrusion rod speed is 0.2-0.6mm / s, the single speed increase is 0.05mm / s, and the speed increase completion time is ≤3min.
[0021] Furthermore, the solution treatment in step S5 adopts a two-stage solution process, wherein the first-stage initial solution temperature is 495±5°C, and the solution time is 4 to 6 hours; the second-stage strengthening solution temperature is 505±5°C, and the solution time is 6 to 8 hours;
[0022] After the solution treatment is completed, the quenching delay time is controlled to be ≤150s during the quenching process, and the water temperature before and after quenching does not exceed 25℃.
[0023] Furthermore, in step S6, the time interval from the completion of quenching to the completion of stretching is ≤ 6 hours.
[0024] Furthermore, in the aging process of step S7, the aging temperature is 175-195° C., and the aging time is 12 hours.
[0025] Compared with the prior art, the beneficial effects of the present invention are:
[0026] (1) The present invention provides a high-strength and high-thermal stability Al-Cu-Mg-Si alloy. From the perspective of dispersion strengthening and precipitation strengthening, the content of Cu and Mg is controlled and the Cu / Mg ratio is adjusted to make the alloy generate S phase as much as possible. In addition, in order to prevent the corrosion resistance from being reduced due to excessive Mg content, the present invention reduces the Mg content and increases the Mn content to ensure the strength of the alloy while ensuring the corrosion resistance. The present invention also adds elements such as Cr and Zr. The Zr element can form Al 3 Zr provides nucleation points to refine the grains, thereby achieving the effect of grain refinement and strengthening. Cr element forms (CrFe)Al in aluminum. 7 and (CrMn)Al 12 The intermetallic compounds such as Mg, Cu, Fe and Ni can hinder the nucleation and growth process of recrystallization, have a certain strengthening effect on the alloy, and can also improve the toughness of the alloy and reduce the sensitivity of stress corrosion cracking; at the same time, the present invention also controls the addition amount and proportion of Mg, Cu, Fe and Ni to control the formation of more heat-resistant phase Al 2 CuMg phase and FeNiAl 9 Phase, which ensures that the alloy has good thermal stability, thereby ensuring that the corrosion resistance and toughness of the aluminum alloy remain at a high level while the strength and thermal stability are improved;
[0027] (2) The present invention provides a high-strength and high-thermal stability Al-Cu-Mg-Si alloy and a preparation method thereof. By adjusting and optimizing the chemical composition of the Al-Cu-Mg-Si alloy, the strength and thermal stability are improved while ensuring toughness and corrosion resistance. The yield strength is ≥475MPa, the tensile strength is ≥540MPa, and the elongation after fracture is ≥12%. After exposure at 200°C for 100h, the tensile strength is ≥210MPa, the yield strength is ≥188MPa, and the exfoliation corrosion grade is EB. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0029] Figure 1 is the equilibrium phase precipitated during the solidification process of the Al-Cu-Mg-Si alloy in Example 1 and its corresponding precipitation temperature;
[0030] Figure 2 Al under different Cu content in Example 1 6 The precipitation temperature and precipitation amount trend of Mn phase during solidification;
[0031] Figure 3 Al under different Cu content in Example 1 2 The precipitation temperature and precipitation amount trend of Cu phase during solidification;
[0032] Figure 4 This is a metallographic photograph of the Al-Cu-Mg-Si alloy profile prepared in Example 2;
[0033] Figure 5 This is a transmission electron microscope photograph of the Al-Cu-Mg-Si alloy prepared in Example 2 in the solid solution state. DETAILED DESCRIPTION
[0034] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0035] Example 1
[0036] In order to solve the problems of insufficient matching degree of strength, toughness and corrosion resistance and poor thermal stability of Al-Cu-Mg-Si alloy profiles for aviation, this embodiment uses a numerical simulation method to optimize the type and content of alloy elements, that is, the chemical composition range of the Al-Cu-Mg-Si alloy is pre-set, and then the relationship between the chemical composition ratio and the performance is simulated by using Jmatpro software, and the optimal chemical composition range of the Al-Cu-Mg-Si alloy is determined according to the matching degree of strength, toughness, corrosion resistance and thermal stability; the specific steps are as follows:
[0037] (1) Based on the analysis of the effects of various alloying elements and the effects of various equilibrium phases in the Al-Cu-Mg-Si alloy, the types of alloying elements added to the alloy are adjusted, and a wider chemical composition range of the Al-Cu-Mg-Si alloy is pre-set, namely Si 0.5-0.9%, Fe≤0.5%, Cu 3.9-5.0%, Mn 0.4-1.2%, Mg 0.2-0.8%, Zr 0.15-0.2%, Cr0.1-0.2%, Ni≤0.1%, Zn≤0.25%, Ti≤0.15%, a single impurity content ≤0.05%, a total impurity content ≤0.15%, and Al as the remainder; a group of determined chemical compositions is selected from them, such as Si 0.6%, Fe 0.2%, Cu4.6%, Mn1.0%, Mg 0.5%, Zr 0.16%, Cr 0.15%, Ni 0.1%, Zn 0.2%, Ti 0.1%, using Jmatpro software for simulation, setting the initial temperature to 700°C, the end temperature to 100°C, obtaining the equilibrium phase and its corresponding precipitation temperature of the Al-Cu-Mg-Si alloy during the solidification process, and obtaining the properties of the Al-Cu-Mg-Si alloy;
[0038] (2) Based on the above ratio, other elements are fixed and only the Cu element is adjusted. The Cu content is taken at different values within the range of 3.9% to 5.0%. The Jmatpro software is used for simulation again to study the equilibrium phases of alloys with different Cu content and their corresponding precipitation temperatures, and obtain the properties of alloys with different Cu content. In addition, one or several equilibrium phases can be extracted from the simulation results to study the change trend of the equilibrium phase under different Cu content.
[0039] (3) Repeat step (2) and adjust other main alloying elements, such as Mg, Mn, etc., in turn, study the equilibrium phases of the alloys with different contents of other main elements and their corresponding precipitation temperatures, and obtain corresponding properties;
[0040] (4) The relationship between different chemical composition ratios and properties is analyzed, and the appropriate chemical composition ratio is determined according to the changes in each phase and the performance change trend. Several groups of tests are carried out based on the determined chemical composition ratio, and samples are taken to test their mechanical properties, corrosion resistance and thermal stability. The optimal chemical composition range of the Al-Cu-Mg-Si alloy is determined based on the matching degree of strength, toughness, corrosion resistance and thermal stability.
[0041] Reference Figure 1-3 , the simulation results of the above-mentioned embodiment 1 are explained, Figure 1 is the equilibrium phase precipitated during the solidification of Al-Cu-Mg-Si alloy and its corresponding precipitation temperature, Figure 2Al at different Cu content 6 The precipitation temperature and precipitation amount of Mn phase during solidification. Figure 3 Al at different Cu content 2 The precipitation temperature and precipitation amount of Cu phase during solidification. Figure 1 The equilibrium phase types that can be precipitated in the solidification process of Al-Cu-Mg-Si alloy can be obtained, and the precipitation temperature corresponding to each equilibrium can be obtained. On this basis, the equilibrium phase that plays a major role in the performance of Al-Cu-Mg-Si alloy can be analyzed, and the main equilibrium phase can be further studied, such as Al 6 Mn phase, Al 2 Cu is equal; from Figure 2 , Figure 3 The Al content under different Cu content can be obtained. 6 Mn phase, Al 2 The precipitation temperature and precipitation amount of Cu phase during solidification are shown in the figure. Figure 2 It can be seen that when the Cu content increases, as the temperature decreases, the Al 6 The change trend of Mn precipitate phase shows a trend of increasing first and then decreasing, and finally increasing sharply to the maximum value and then tending to equilibrium. There is no precipitation zone between 610℃ and 140℃. At the same time, when the Cu content is 3.9-5.0%, the change trend tends to be consistent. There is Al between 140℃ and 100℃. 6 The Mn precipitation phase increases rapidly; Figure 3 It can be seen that when the Cu content increases, as the temperature decreases, the Al 2 The content of Cu precipitated phase shows a continuous increase trend, the increase rate is fast at first and then slow, and finally it increases sharply to the maximum value and then tends to balance. When the Cu content is in the range of 3.9-5.0%, Al precipitates in the range of 520-100℃. 2 Cu, the precipitation rate is basically the same, but as the Cu content increases from 3.9% to 4.8%, Al 2 The amount of Cu precipitation also gradually increases. When the Cu content is 5.0, Al 2 The amount of Cu precipitation decreased slightly.
[0042] In addition, Jmatpro software can also be used to obtain the trend of mechanical properties under different Cu content. When the Mg content remains unchanged, the Cu content is within the range of 3.9-5.0%. As the Cu content increases, the tensile strength of the alloy increases, and the elongation does not change significantly; but if the Cu content is too high, it will promote Al 2Cu and AlCuMgMn phases precipitate, thereby increasing the potential difference between the matrix and the second phase, resulting in a decrease in corrosion resistance. In order to obtain a range of alloy elements that match strength, toughness and corrosion resistance and have good thermal stability, further pilot tests were conducted to obtain actual mechanical properties, corrosion resistance and thermal stability data to obtain a better range of alloy elements.
[0043] In this embodiment, the change of Cu element content is taken as an example. Based on the above simulation, several groups of representative alloy ranges are selected, as shown in Table 1 below. The corresponding alloys are prepared by the same melting, homogenization and extrusion processes through pilot tests, and their mechanical properties, corrosion resistance and thermal stability are obtained, as shown in Table 2.
[0044] Table 1
[0045]
[0046]
[0047] Table 2
[0048]
[0049] The above experimental test results are consistent with the changing trend of the simulation calculation results. Although the strength increases with the increase of Cu content, the corrosion resistance decreases significantly. Therefore, the preferred range of the selected Cu element content is 4.4-4.8%.
[0050] Based on the technical problem to be solved by the present invention, when analyzing the above numerical simulation results, that is, the precipitation amount of the equilibrium phase and the performance change trend under different chemical compositions, this embodiment mainly considers increasing the S phase (Al 2 CuMg) content to ensure its high strength and toughness, while reducing Al 2 The content of precipitated phases such as Cu and AlCuMnSi is analyzed to reduce the potential difference between the second phase and the matrix to ensure its corrosion resistance. 3 The change of Zr precipitation phase is expected to utilize Al 3 Zr precipitation phase can refine the grain structure and achieve the effect of fine grain strengthening; and analyze (CrFe)Al 7 and (CrMn)Al 12 The precipitation of intermetallic compounds such as (CrFe)Al 7 and (CrMn)Al 12 The nucleation and growth process of recrystallization is hindered, the microstructure is improved, the toughness of the alloy is increased, and the sensitivity to stress corrosion cracking is reduced; in addition, this embodiment also needs to obtain good thermal stability. The main heat-resistant phase in this type of alloy is S (Al 2 CuMg) phase, FeNiAl9 phase, in order to obtain high thermal stability, it is necessary to control S(Al 2 CuMg) phase, FeNiAl 9 Phase generation.
[0051] This embodiment analyzes the above numerical simulation results, analyzes the role of each main alloying element in the Al-Cu-Mg-Si alloy, and combines the pilot test data to determine the chemical composition range of the alloy, specifically:
[0052] As an important alloying element, Cu has a major influence on strength and toughness due to the strengthening phase Al. 2 Cu、Al 2 CuMg is related to Vickers hardness. In addition, the content of Cu also has a significant effect on Vickers hardness. When the Cu / Mg ratio remains unchanged, the room temperature tensile strength and hardness of the alloy increase significantly with the increase of Cu and Mg content, and the elongation decreases slightly; when the Mg content remains unchanged, the tensile strength and hardness of the alloy increase significantly with the increase of Cu / Mg, and the elongation does not change significantly. However, excessive Cu content will promote Al 2 Cu and AlCuMgMn phases precipitate, thereby increasing the potential difference between the matrix and the second phase, resulting in a decrease in corrosion resistance. Combining the simulation calculation results and the pilot test data, the range of Cu element is selected to be 3.9-5.0%, preferably 4.4-4.8%; in addition, the Cu / Mg ratio needs to be controlled to 8.0-10.0 to promote Al 2 CuMg precipitation, reducing Al 2 Cu and AlCuMgMn precipitate;
[0053] As an important strengthening element, Mg is particularly effective in improving the aging mechanical properties of Al-Cu-Mg alloy, but at the same time it will reduce the elongation of the alloy. Mg has a more obvious effect on the cast structure. When the Mg and Zn content is too high, more dendrites will be formed inside the matrix, which is difficult to eliminate by subsequent homogenization annealing. At the same time, Mg, as an important component of the strengthening phase, also has a certain effect on the mechanical properties and electrical conductivity of the cast aluminum alloy. From the perspective of dispersion strengthening and precipitation strengthening, it is necessary to make the alloy generate the strengthening phase S phase as much as possible to improve its aging strength. However, Mg ≥ 0.6% will promote the formation of residual crystalline phase and Cu-rich aging precipitation phase, increase the width of PFZ, increase the potential difference between the cathode and the anode, and accelerate corrosion. Combined with the simulation calculation results of this embodiment, with the increase of Mg content, the mechanical properties of Al-Cu-Mg-Si alloy show a trend of first increasing and then decreasing. Therefore, we use Mn element to strengthen part of the strengthening effect, which can achieve the effect of reducing the Mg content, thereby ensuring the toughness and corrosion resistance of the alloy; In addition, the main heat-resistant phase in this type of alloy is S (Al2 CuMg) phase, in order to obtain good thermal stability, the Mg content cannot be too low, and the Mg content should be appropriately increased so that the alloy composition falls within the α(Al)+S+Al in the Al-Cu-Mg system ternary equilibrium diagram. 2 Cu three-phase region, as much S (Al 2 CuMg) phase. Therefore, the Mg content is selected to be 0.2-0.8%, the Mn content is 0.4-1.2%, preferably, the Mg content is 0.46-0.6%, and the Mn content is 0.8-1.1%;
[0054] Fe and Si impurity elements are generally unavoidable and tend to form coarse and insoluble Al phases. 7 Cu 2 Fe, Mg 2 Si, etc., especially in alloys with high Cu elements, Fe and Si generally exist in these two forms, and these two phases will consume part of the strengthening elements during the formation process, so Fe and Si have a great influence on the strength, plasticity and toughness, electrical conductivity, quenching sensitivity of the alloy, especially the strength and plasticity of large wall thickness, but in Al-Cu-Mg-Si alloy, Si element can promote the formation of strengthening phase Q phase. Combined with the actual production cost, numerical simulation results and pilot test data, the selected Fe≤0.5%, Si content is 0.5-0.9%, preferably Fe≤0.3%, Si content is 0.6-0.8%;
[0055] In this alloy, Fe and Ni also have a good effect on the heat resistance of the alloy, but adding iron and nickel alone will reduce the heat resistance of the alloy. Appropriate addition of nickel can prevent Cu 2 FeAl 2 、CuFeAl 3 The formation of phase, but too much addition will form AlCu x Ni y By controlling Fe / Ni≤2.5, they are finally combined to form FeNiAl with good heat resistance. 9 phase, so that the Cu in the alloy can fully form a large amount of S (Al 2 CuMg) phase, thus ensuring the alloy has good thermal stability;
[0056] Ti is a commonly used additive element in aluminum alloys and is added in the form of Al-Ti or Al-Ti-B master alloys. 2 Phase, which becomes the non-spontaneous core during crystallization and plays a role in refining the casting structure;
[0057] This embodiment also adds Zr and Cr elements, wherein Zr element can form Al 3Zr provides nucleation points and plays a role in grain refinement. However, if the Zr content is too high, coarse Al 3 Zr primary phase, thereby reducing the Zr content dissolved in the matrix during alloy solidification, thereby reducing the beneficial effect of Zr. Combined with the numerical simulation results, the range of Zr element is selected to be 0.15-0.2%, preferably 0.15-0.18%; Cr element forms (CrFe)Al in aluminum 7 and (CrMn)Al 12 Intermetallic compounds such as Cr can hinder the nucleation and growth process of recrystallization, have a certain strengthening effect on the alloy, and can also improve the toughness of the alloy and reduce the sensitivity to stress corrosion cracking. However, calculation results show that its addition amount should not exceed 0.35%. Exceeding this content will lead to the formation of coarse Cr-containing compounds and reduce the plasticity and formability of the alloy. Therefore, the range of Cr element is selected to be 0.1-0.2%, preferably 0.1-0.15%.
[0058] By analyzing the above numerical simulation results and the role of each main alloying element in the Al-Cu-Mg-Si alloy, the chemical composition range of the Al-Cu-Mg-Si alloy is obtained as follows: Si 0.5-0.9%, Fe≤0.5%, Cu 3.9-5.0%, Mn 0.4-1.2%, Mg 0.2-0.8%, Zr 0.15-0.2%, Cr 0.1-0.2%, Ni≤0.1%, Zn≤0.25%, Ti≤0.15%, single impurity content≤0.05%, total impurity content≤0.15%, Al is the balance; preferably Si0.6-0.8%, Fe≤0.3%, Cu 4.4-4.8%, Mn 0.8-1.1%, Mg 0.45-0.6%, Zr 0.15-0.18%, Cr 0.1~0.15%, Ni≤0.1%, Zn≤0.2%, Ti≤0.1%, individual impurity content≤0.05%, total impurity content≤0.15%, Al is the balance.
[0059] This embodiment uses numerical simulation to calculate the simulation results of chemical composition-performance, which can save a lot of trial and error time and cost in the early stage of composition design. This embodiment optimizes and adjusts the chemical composition of the alloy to obtain a high-strength and high-thermal stability Al-Cu-Mg-Si alloy. The alloy can have high strength and high thermal stability while ensuring toughness and corrosion resistance. The yield strength of the alloy is ≥475MPa, the tensile strength is ≥540MPa, and the elongation after fracture is ≥12%; and after exposure at 200°C for 100h, its tensile strength is ≥210MPa, the yield strength is ≥188MPa, and the exfoliation corrosion grade is EB.
[0060] Example 2
[0061] Based on the chemical composition range of the Al-Cu-Mg-Si alloy determined in Example 1, this example prepares an Al-Cu-Mg-Si alloy profile and performs performance testing.
[0062] The chemical composition of the Al-Cu-Mg-Si alloy in this embodiment is: Si 0.6%, Fe 0.3%, Cu 4.4%, Mn 0.8%, Mg 0.45%, Zr 0.15%, Cr 0.1%, Ni 0.08%, Zn 0.17%, Ti 0.09%, and the balance is Al.
[0063] The preparation method of the Al-Cu-Mg-Si alloy in this embodiment comprises the following steps:
[0064] S1. According to the chemical composition ratio of the Al-Cu-Mg-Si alloy, pure Al, Cu plate, Mg ingot, Al-Si master alloy, Al-Mn master alloy, Al-Zr master alloy, Al-Cr, Al-Ti master alloy and Al-Ni are weighed as raw materials;
[0065] S2. Melt and cast the above raw materials, wherein the furnace temperature setting value in the smelting furnace is ≤1060°C, and electromagnetic stirring is turned on when the melt temperature reaches 700°C after the charge is leveled. After all the raw materials in the melting furnace are melted, the melt temperature is measured and slag is removed, Mg ingots are added, stirred, slag is removed, and sampling is performed. The melt stays in the smelting furnace for 5 hours to obtain aluminum alloy molten liquid; then the melt is transferred from the smelting furnace to the refining furnace, at which time the melt temperature in the smelting furnace is 744°C. After refining, casting is performed under the casting process parameters of casting water temperature of 19°C, starting casting temperature of 741°C, casting temperature of 700°C, casting speed of 33mm / min, water flow of 37 / m3 / h, and casting temperature of the hot end of the flow plate of 697°C to obtain a large-sized ingot with a diameter of φ600mm and a length of 12m;
[0066] S3. The Al-Cu-Mg-Si alloy ingot is homogenized, and the homogenization process adopts a two-stage homogenization process, and the ingot stacking direction is consistent with the circulating air direction of the soaking furnace; specifically, the first stage homogenization is heated to 485°C at a heating rate of 40°C / h and kept warm for 12 hours; the second stage homogenization is heated to 495°C at a heating rate of 20°C / h and kept warm for 5 hours, and then air-cooled to room temperature after being taken out of the furnace; the two-stage homogenization process adopted in this embodiment can make the coarse precipitates in the crystal dissolve more thoroughly, and the size and number of the eutectic phase in the crystal are further reduced, so that the structure is more uniform, thereby improving the performance of the material, wherein the first stage homogenization is mainly used to eliminate segregation and prevent local overburning, and the second stage homogenization can fully eliminate component segregation and dissolve micron-sized phases to the maximum extent;
[0067] S4. Saw the homogenized Al-Cu-Mg-Si alloy ingot into aluminum rods, and perform hot extrusion to obtain extruded profiles; in the hot extrusion, the diameter of the extrusion barrel is 600 mm, the set temperature of the extrusion barrel is 420° C., the temperature of the inner layer 1-4 zone is controlled at 410-421° C., the mold insulation temperature is 400° C., the insulation time is 5 h, the aluminum rod insulation temperature is 380° C., the extrusion rod speed is 0.4 mm / s, the single speed-up amount is 0.05 mm / s, the speed-up completion time is 159 s, and an extruded profile with a wall thickness of 150 mm is obtained by extrusion;
[0068] S5. The extruded profile is subjected to solution treatment at the solution temperature, and quenched to room temperature after the solution treatment is completed; the solution treatment adopts a two-stage solution process, the first stage initial solution temperature is 495°C, the solution time is 4h; the second stage strengthening solution temperature is 505°C, and the solution time is 7h; after the solution treatment is completed, water quenching to room temperature, the quenching delay time is ≤85s, and the water temperature before and after solution quenching does not exceed 25°C;
[0069] S6. Perform stretching and straightening treatment on the extruded profile after solution treatment and quenching treatment, set the stretching rate to 2.0%, the stretching speed to 120 mm / s, the clamping force to 100 t, and the time interval from the completion of quenching to the completion of stretching to ≤ 6 h;
[0070] S7. The stretched extruded profile is subjected to aging treatment at a temperature of 180° C. for 12 h, followed by air cooling to room temperature to obtain an Al-Cu-Mg-Si alloy profile.
[0071] After testing, the yield strength of the above-mentioned Al-Cu-Mg-Si alloy profile is 482MPa, the tensile strength is 545MPa, and the elongation after fracture is 12.5%. After the profile is exposed at 200°C for 100h, its tensile strength is 222MPa, the yield strength is 189MPa, and the exfoliation corrosion grade is EB.
[0072] In addition, the Al-Cu-Mg-Si alloy profile prepared in this embodiment was sampled for metallographic examination. Figure 4 As shown, from Figure 4 It can be seen that the alloy grain structure is evenly distributed, and no large-sized second phase, voids, or micro-porosity defects are found.
[0073] In addition, the Al-Cu-Mg-Si alloy prepared in this embodiment was sampled in the solid solution state and detected using a transmission electron microscope. Figure 5 As shown, from Figure 5It can be seen that in the solid state, the S phase is fully dissolved in the Al matrix. At the same time, except for a small amount of large-sized S phase in the grains and on the grain boundaries that has not been re-dissolved, the rest of the second phases are also fully dissolved into the Al matrix, which lays a good foundation for subsequent aging strengthening and the overall preparation of the material.
[0074] Example 3
[0075] The chemical composition of the Al-Cu-Mg-Si alloy in this embodiment is: Si 0.6%, Fe 0.3%, Cu 4.4%, Mn 0.8%, Mg 0.45%, Zr 0.15%, Cr 0.1%, Ni 0.08%, Zn 0.17%, Ti 0.09%, and the balance is Al.
[0076] The preparation method of the Al-Cu-Mg-Si alloy in this embodiment comprises the following steps:
[0077] S1. According to the chemical composition ratio of the Al-Cu-Mg-Si alloy, pure Al, Cu plate, Mg ingot, Al-Si master alloy, Al-Mn master alloy, Al-Zr master alloy, Al-Cr, Al-Ti master alloy and Al-Ni are weighed as raw materials;
[0078] S2. Melt and cast the above raw materials, wherein the furnace temperature setting value in the melting furnace is ≤1060°C. After all the raw materials in the melting furnace are melted, measure the melt temperature and perform slag removal, add Mg ingots, stir, slag removal, and sampling. The melt stays in the melting furnace for 5 hours to obtain aluminum alloy molten liquid; then transfer the melt from the melting furnace to the refining furnace. At this time, the melt temperature in the melting furnace is 745°C. After refining, the casting water temperature is 22°C, the starting casting temperature is 739°C, the casting temperature is 698°C, the casting speed is 31mm / min, and the water flow rate is 36 / m 3 / h, and a casting temperature of 700°C at the hot end of the flow plate, to obtain a large-sized ingot with a diameter of φ600mm and a length of 11.7m;
[0079] S3. The Al-Cu-Mg-Si alloy ingot is homogenized, and the homogenization process adopts a two-stage homogenization process, and the ingot stacking direction is consistent with the circulating air direction of the soaking furnace; specifically, the first stage homogenization is heated to 485°C at a heating rate of 40°C / h and kept warm for 11 hours; the second stage homogenization is heated to 494°C at a heating rate of 20°C / h and kept warm for 6 hours, and then air-cooled to room temperature after being taken out of the furnace; the two-stage homogenization process adopted in this embodiment can make the coarse precipitates in the crystal dissolve more thoroughly, and the size and number of the eutectic phase in the crystal are further reduced, so that the structure is more uniform, thereby improving the performance of the material, wherein the first stage homogenization is mainly used to eliminate segregation and prevent local overburning, and the second stage homogenization can fully eliminate component segregation and dissolve micron-sized phases to the maximum extent;
[0080] S4. Saw the homogenized Al-Cu-Mg-Si alloy ingot into aluminum rods, and perform hot extrusion to obtain extruded profiles; in the hot extrusion, the diameter of the extrusion barrel is 600 mm, the set temperature of the extrusion barrel is 420° C., the temperature of the inner layer 1-4 zone is controlled at 408-423° C., the mold insulation temperature is 385° C., the insulation time is 18 h, the aluminum rod insulation temperature is 400° C., the extrusion rod speed is 0.4 mm / s, the single speed-up amount is 0.05 mm / s, the speed-up completion time is 128 s, and the extruded profile with a wall thickness of 150 mm is obtained by extrusion;
[0081] S5. The extruded profile is subjected to solution treatment at the solution temperature, and quenched to room temperature after the solution treatment is completed; the solution treatment adopts a two-stage solution process, the first stage initial solution temperature is 495°C, the solution time is 5h; the second stage strengthening solution temperature is 505°C, and the solution time is 8h; after the solution treatment is completed, water quenching to room temperature, the quenching delay time is ≤93s, and the water temperature before and after solution quenching does not exceed 25°C;
[0082] S6. Perform stretching and straightening treatment on the extruded profile after solution treatment and quenching treatment, set the stretching rate to 2.0%, the stretching speed to 120 mm / s, the clamping force to 100 t, and the time interval from the completion of quenching to the completion of stretching to ≤ 6 h;
[0083] S7. The stretched extruded profile is subjected to aging treatment at a temperature of 190° C. for 10 h, followed by air cooling to room temperature to obtain an Al-Cu-Mg-Si alloy profile.
[0084] After testing, the yield strength of the above-mentioned Al-Cu-Mg-Si alloy profile is 490MPa, the tensile strength is 542MPa, and the elongation after fracture is 12.0%. After the profile is exposed at 200°C for 100h, its tensile strength is 222MPa, the yield strength is 191MPa, and the exfoliation corrosion grade is EB.
[0085] Example 4
[0086] The difference between this embodiment and embodiment 2 is that the chemical composition of the Al-Cu-Mg-Si alloy in this embodiment is: Si 0.8%, Fe 0.3%, Cu 4.8%, Mn 1.1%, Mg 0.6%, Zr 0.18%, Cr 0.15%, Ni 0.08%, Zn 0.20%, Ti 0.09%, and the balance is Al.
[0087] The preparation method of the Al-Cu-Mg-Si alloy in this embodiment comprises the following steps:
[0088] S1. According to the chemical composition ratio of the Al-Cu-Mg-Si alloy, pure Al, Cu plate, Mg ingot, Al-Si master alloy, Al-Mn master alloy, Al-Zr master alloy, Al-Cr, Al-Ti master alloy and Al-Ni are weighed as raw materials;
[0089] S2. Melt and cast the above raw materials, wherein the furnace temperature setting value in the melting furnace is ≤1060°C. After all the raw materials in the melting furnace are melted, measure the melt temperature and perform slag removal, add Mg ingots, stir, slag removal, and sampling. The melt stays in the melting furnace for 5 hours to obtain aluminum alloy molten liquid; then transfer the melt from the melting furnace to the refining furnace. At this time, the melt temperature in the melting furnace is 745°C. After refining, the casting water temperature is 22°C, the starting casting temperature is 739°C, the casting temperature is 698°C, the casting speed is 31mm / min, and the water flow rate is 36 / m 3 / h, and a casting temperature of 700°C at the hot end of the flow plate, to obtain a large-sized ingot with a diameter of φ600mm and a length of 12.0m;
[0090] S3. The Al-Cu-Mg-Si alloy ingot is homogenized, and the homogenization process adopts a two-stage homogenization process, and the ingot stacking direction is consistent with the circulating air direction of the soaking furnace; specifically, the first stage homogenization is heated to 485°C at a heating rate of 40°C / h and kept warm for 11 hours; the second stage homogenization is heated to 494°C at a heating rate of 20°C / h and kept warm for 6 hours, and then air-cooled to room temperature after being taken out of the furnace; the two-stage homogenization process adopted in this embodiment can make the coarse precipitates in the crystal dissolve more thoroughly, and the size and number of the eutectic phase in the crystal are further reduced, so that the structure is more uniform, thereby improving the performance of the material, wherein the first stage homogenization is mainly used to eliminate segregation and prevent local overburning, and the second stage homogenization can fully eliminate component segregation and dissolve micron-sized phases to the maximum extent;
[0091] S4. Saw the homogenized Al-Cu-Mg-Si alloy ingot into aluminum rods and perform hot extrusion to obtain extruded profiles; in the hot extrusion, the diameter of the extrusion barrel is 600 mm, the set temperature of the extrusion barrel is 420° C., the temperature of the inner layer 1-4 zone is controlled at 408-423° C., the mold insulation temperature is 415° C., the insulation time is 36 h, the aluminum rod insulation temperature is 435° C., the extrusion rod speed is 0.4 mm / s, the single speed-up amount is 0.05 mm / s, the speed-up completion time is 130 s, and the extruded profile with a wall thickness of 150 mm is obtained by extrusion;
[0092] S5. The extruded profile is subjected to solution treatment at the solution temperature, and quenched to room temperature after the solution treatment is completed; the solution treatment adopts a two-stage solution process, the first stage initial solution temperature is 495°C, the solution time is 5h; the second stage strengthening solution temperature is 505°C, and the solution time is 8h; after the solution treatment is completed, water quenching to room temperature, the quenching delay time is ≤93s, and the water temperature before and after solution quenching does not exceed 25°C;
[0093] S6. Perform stretching and straightening treatment on the extruded profile after solution treatment and quenching treatment, set the stretching rate to 2.0%, the stretching speed to 120 mm / s, the clamping force to 100 t, and the time interval from the completion of quenching to the completion of stretching to ≤ 6 h;
[0094] S7. The stretched extruded profile is subjected to aging treatment at a temperature of 190° C. for 10 h, followed by air cooling to room temperature to obtain an Al-Cu-Mg-Si alloy profile.
[0095] After testing, the yield strength of the above-mentioned Al-Cu-Mg-Si alloy profile is 485MPa, the tensile strength is 546MPa, and the elongation after fracture is 12.5%. After the profile is exposed at 200°C for 100h, its tensile strength is 219MPa, the yield strength is 193MPa, and the exfoliation corrosion grade is EB.
[0096] Comparative Example 1
[0097] The difference between this comparative example and Example 2 is that the chemical composition of the Al-Cu-Mg-Si alloy in this comparative example is: Si 0.9%, Fe 0.3%, Cu 5.2%, Mn 1.2%, Mg 0.3%, Cr 0.1%, Zn 0.17%, Ti 0.09%, and the balance is Al.
[0098] After testing, the yield strength of the above-mentioned Al-Cu-Mg-Si alloy profile is 505MPa, the tensile strength is 578MPa, and the elongation after fracture is 12%. After the profile is exposed at 200°C for 100h, its tensile strength is 220MPa, the yield strength is 198MPa, and the exfoliation corrosion grade is ED.
[0099] It should be noted that some parts not described in the present invention can be implemented by adopting or drawing on existing technologies.
[0100] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A high-strength and high-thermal stability Al-Cu-Mg-Si alloy, characterized in that: The chemical composition and mass percentage of the alloy are: Si 0.5-0.9%, Fe≤0.5%, Cu 3.9-4.8%, Mn 0.4-1.2%, Mg 0.2-0.8%, Zr0.15-0.2%, Cr 0.1-0.2%, Ni≤0.1%, Zn≤0.25%, Ti≤0.15%, the content of a single impurity is ≤0.05%, the total impurity content is ≤0.15%, and Al is the balance.
2. The high-strength and high-thermal-stability Al-Cu-Mg-Si alloy according to claim 1, characterized in that: The chemical composition and mass percentage of the alloy are: Si 0.6-0.8%, Fe≤0.3%, Cu 4.4-4.8%, Mn 0.8-1.1%, Mg 0.45-0.6%, Zr 0.15-0.18%, Cr 0.1-0.15%, Ni≤0.1%, Zn≤0.2%, Ti≤0.1%, the content of a single impurity is ≤0.05%, the total impurity content is ≤0.15%, and Al is the balance.
3. The high-strength and high-thermal-stability Al-Cu-Mg-Si alloy according to claim 1 or 2, characterized in that: The yield strength of Al-Cu-Mg-Si alloy is ≥475MPa, the tensile strength is ≥540MPa, and the elongation after fracture is ≥12%; and after exposure at 200°C for 100h, its tensile strength is ≥210MPa, the yield strength is ≥188MPa, and the exfoliation corrosion grade is EB.
4. A method for preparing a high-strength and high-thermal stability Al-Cu-Mg-Si alloy according to any one of claims 1 to 3, characterized in that: Includes steps: S1. Preset the chemical composition range of Al-Cu-Mg-Si alloy, then use Jmatpro software to simulate the relationship between chemical composition ratio and performance, and determine the optimal chemical composition range of Al-Cu-Mg-Si alloy according to the matching degree of strength, toughness, corrosion resistance and thermal stability; S2, according to the chemical composition range determined in step S1, the raw materials are melted and cast to obtain an Al-Cu-Mg-Si alloy ingot; S3, homogenizing the Al-Cu-Mg-Si alloy ingot; S4, sawing the homogenized Al-Cu-Mg-Si alloy ingot into aluminum bars, and hot extruding them to obtain extruded profiles; S5, performing a solution treatment on the extruded profile at a solution temperature, and quenching to room temperature after the solution treatment; S6, stretching and straightening the extruded profile after solution treatment and quenching treatment; S7. Performing aging treatment on the stretched extruded profile, and then air-cooling to room temperature to obtain an Al-Cu-Mg-Si alloy profile.
5. The method for preparing a high-strength and high-thermal stability Al-Cu-Mg-Si alloy according to claim 4, characterized in that: In step S2, the melt temperature is controlled to be ≤745°C during the smelting process, and the melt temperature in the smelting furnace before transferring the melt from the smelting furnace to the refining furnace is 740±5°C; the melt temperature of the charge reaches 700°C as the start time of the melt staying in the smelting furnace, and the start time of the converter is the end time of the melt staying in the smelting furnace. The melt staying time in the smelting furnace is controlled not to exceed 8 hours, and re-stirring and sampling are required if the specified time is exceeded; During the casting process, the casting water temperature is 18-23°C, the starting temperature is 735-745°C, the casting temperature is 685-705°C, the casting speed is 31-35mm / min, and the water flow rate is 34-40m 3 / h; and during the casting process, the aluminum liquid temperature at the outlet of the holding furnace is controlled to be ≤750℃, and the casting temperature at the hot end of the flow plate is 695±10℃.
6. The method for preparing a high-strength and high-thermal stability Al-Cu-Mg-Si alloy according to claim 4, characterized in that: In step S3, the homogenization treatment adopts a two-stage homogenization process. The first stage is heated to 485±5°C at a heating rate of 35-50°C / h and kept warm for 10-12h; the second stage is heated to 495±5°C at a heating rate of 15-25°C / h and kept warm for 5-8h.
7. The method for preparing a high-strength and high-thermal stability Al-Cu-Mg-Si alloy according to claim 4, characterized in that: In step S4, during hot extrusion, the mold insulation temperature is set to 385-415° C., the insulation time is set to 4-36 hours, the inner layer heating temperature of the extrusion barrel is set to 405-435° C., the aluminum rod insulation temperature is set to 370-400° C., the extrusion rod speed is set to 0.2-0.6 mm / s, the single speed increase is set to 0.05 mm / s, and the speed increase completion time is ≤3 min.
8. The method for preparing a high-strength and high-thermal stability Al-Cu-Mg-Si alloy according to claim 4, characterized in that: The solution treatment in step S5 adopts a two-stage solution treatment process, wherein the initial solution treatment temperature of the first stage is 495±5°C and the solution treatment time is 4 to 6 hours; the strengthening solution treatment temperature of the second stage is 505±5°C and the solution treatment time is 6 to 8 hours; After the solution treatment is completed, the quenching delay time is controlled to be ≤150s during the quenching process, and the water temperature before and after quenching does not exceed 25℃.
9. The method for preparing a high-strength and high-thermal stability Al-Cu-Mg-Si alloy according to claim 4, characterized in that: The time interval from the completion of quenching to the completion of stretching in step S6 is ≤ 6 hours.
10. The method for preparing a high-strength and high-thermal-stability Al-Cu-Mg-Si alloy according to claim 4, characterized in that: In the aging process of step S7, the aging temperature is 175-195° C. and the aging time is 12 hours.
Citation Information
Patent Citations
Al-Cu-Mg alloy suitable for aerospace application
CN101297054A
High strength and high heat resistant aluminum alloy material and preparation method thereof
CN104711468A
Aluminum alloy plate and manufacturing method thereof
CN106893909A
Aluminum-copper alloy and casting method thereof
CN107099710A
Preparation method for aluminum alloy material
CN107164646A
Cited By
Cast aluminum alloy and preparation method thereof
CN120888818A